2015
DOI: 10.1016/j.hlc.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Aspiration Thrombectomy in Treatment of Massive Pulmonary Embolism

Abstract: This study demonstrates safety and effectiveness of percutaneous mechanical aspiration thrombectomy in patients with massive PE with a large thrombus burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Rheolytic aspiration thrombectomy carries a black box warning for use in pulmonary embolus in spite of several small case series describing the efficacy of rheolytic aspiration thrombectomy for PE 6 . Continuous aspiration thrombectomy has been shown to be feasible for more conventional PE in small case series and represents the only alternative when open thrombectomy, CDT, or systemic thrombolysis is contraindicated 7, 8, 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheolytic aspiration thrombectomy carries a black box warning for use in pulmonary embolus in spite of several small case series describing the efficacy of rheolytic aspiration thrombectomy for PE 6 . Continuous aspiration thrombectomy has been shown to be feasible for more conventional PE in small case series and represents the only alternative when open thrombectomy, CDT, or systemic thrombolysis is contraindicated 7, 8, 9…”
Section: Discussionmentioning
confidence: 99%
“…Whereas IVC tumor thrombosis is common in patients with locally advanced RCC, massive embolism is a rare occurrence 8 . In a retrospective analysis, of 13 patients treated with large IVC tumor thrombus associated with RCC, only one patient had a documented embolism of the tumor thrombus 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, in the presence of contraindications to systemic thrombolysis, the degree of refractory hypoxaemia and RV dysfunction at presentation are a solid indication. Moreover, as a previous study demonstrated, percutaneous mechanical aspiration thrombectomy in patients with massive PE with large thrombus burden is safe and effective [6].…”
Section: Clinical Spotlightmentioning
confidence: 77%
“…Although systemic anticoagulation remains the cornerstone of therapy for acute symptomatic pulmonary embolism, the morbidity and mortality associated with massive pulmonary embolism (MPE) and submassive pulmonary embolism (SPE) warrant treatment beyond anticoagulation alone. More aggressive therapeutic options include systemic intravenous thrombolysis, surgical embolectomy, catheter‐directed intra‐arterial thrombolysis, and percutaneous mechanical thrombectomy (PMT) . Despite major advancements in endovascular technology, the role of PMT in the treatment of acute pulmonary embolism remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…More aggressive therapeutic options include systemic intravenous thrombolysis, surgical embolectomy, catheter-directed intraarterial thrombolysis, and percutaneous mechanical thrombectomy (PMT). 6,7 Despite major advancements in endovascular technology, the role of PMT in the treatment of acute pulmonary embolism remains undefined.…”
Section: Introductionmentioning
confidence: 99%